Description of the novel HLA‐DPB1*137:01 allele found in an Italian subject. (3rd May 2013) - Cosentini, E.; Frison, S.; Longhi, E.; Luongo, V.; Ciardiello, G.; Bruno, P.; Mantovani, M.
Summary In this report, we describe the identification and sequencing of a novel HLA‐DPB1 allele, found in an Italian haematological patient. This allele is identical to DPB1*17:01 except for a single nucleotide substitution (GAC→GAG) at position 57, which changes the encoded amino acid from Asp to Glu.